Cortical Morphological Changes in Congenital Amusia: Surface-Based Analyses - Liao, Xuan; Sun, Junjie; Jin, Zhishuai; Wu, DaXing; Liu, Jun (Frontiers in Psychiatry, 2022)
Background: Congenital amusia (CA) is a rare disorder characterized by deficits in pitch perception, and many structural and functional magnetic resonance study have been proposed to learn about the neural bases of this disease, but a structural MRI analysis using surface-based morphology (SBM) method is not performed to identify regions with cortical features abnormalities at the vertex-based level. Methods: 15 participants with CA and 13 healthy controls (HCs) underwent structural magnetic resonance imaging. A surface-based morphology method was used to identify anatomical abnormalities. And then, we extracted and compared the surface parameters mean value of the identified clusters with statistically significant inter-group differences, Finally, we used a Pearson’s correlation analysis to assess the correlation between the Montreal Battery of Evaluation of Amusia scores (MBEA) and surface parameters. Results: The CA group had significantly lower scores on the MBEA compared to HCs (P=0.000). Results also indicated the significant increases of fractal dimension in the right caudal middle frontal gyrus (P<0.05. false discovery rate (FDR)-corrected at the cluster level) and decrease of sulcal depth in the right pars triangularis gyrus (P<0.05. false discovery rate (FDR)-corrected at the cluster level) of CA subjects compared to HCs, and a negative correlation between the averaged fractal dimension values in the right caudal middle frontal gyrus and MEBA subtest, including violate key (r=-0.5712, P=0.0015), pitch contour (r=-0.4662, P=0.0124), pitch interval (r=-0.4564, P=0.0146), rhythmic discrimination (r=-0.5133, P=0.0052), metre (r=-0.3937, P=0.0382), and memory (r=-0.3879, P=0.0414), and a significant positive correlation between the mean value of sulcal depth in the right pars triangularis gyrus and MEBA subtests, including violate key (r=0.5328, P=0.0035), pitch interval (r=0.4059, P=0.0321), rhythmic discrimination (r=0.5733, P=0.0014), metre (r=0.5061,P=0.0060), and memory (r=0.4001, P=0.0349). Conclusion: We identified the brain regions associated with language, i.e., the right middle frontal gyrus and the right pars triangular gyrus, implicated in CA. Our research demonstrated anatomically that CA is a disorder involving speech disorders, such as verbal memory and verbal fluency